THE EFFECT OF ROLE PLAYING MODEL ON LEARNING OUTCOMES IN THE SUB-THEME GRATEFUL FOR STUDENT DIVERSITY - Maria Barus; Selamat Triadil Saragih; Minar Trisnawati Tobing (Sensei International Journal of Education and Linguistic, 2023)
The background of this research is that student learning outcomes are still low and have not reached the minimum completeness criteria (KKM). The lack of creativity of teachers using models in learning the sub-theme of gratitude for the diversity of class IV UPTD Negeri 122371 Pematang Siantar. And students are less enthusiastic when the teaching and learning process takes place. The purpose of this study was to determine the effect of the Role Playing Model on Student Learning Outcomes in the Sub-theme of Gratitude for the Diversity of Class IV UPTD Negeri 122371 Pematang Siantar. The design of this study uses the type of Pre-Experimental research with one group pretest posttest design. In this study the population was all students of class IV UPTD Negeri 122371 Pematang Siantar, totaling 30 students. The data collection technique used is the test. The results of testing the hypothesis using the paired sample t-test technique with the help of the SPSS 23 program, based on the calculation results that the 2-tailed significant value is 0.00 <0.05 or by comparing t-count > t-table with df = (n-1 ) namely 9.748> 2.045 then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the role-playing model on learning outcomes in the sub-theme of being grateful for the diversity of grade IV UPTD Negeri 122371 Pematang Siantar students.